2009
DOI: 10.1253/circj.cj-08-0755
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Changes in Coronary Plaque Associated With Atorvastatin Therapy

Abstract: Circ J 2009; 73: 718 -725 here have been many reports that intensive lowering of low-density lipoprotein-cholesterol (LDL-C) with 3-hydroxy-3-methylglutaryl-coenzyme A (HMGCoA) reductase inhibitors (statins) is effective in preventing cardiovascular events. [1][2][3] Although the mechanism by which statins confer cardiovascular benefit is not precisely understood, regression of coronary plaque volume and reduction of plaque vulnerability are presumed to play important roles. Angioscopic observations have sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 31 publications
5
64
0
1
Order By: Relevance
“…The details of this procedure and its reproducibility were previously described. 5 IUVS measurements were performed with a 2.6F, 40-MHz Atlantis Pro IVUS catheter (Boston Scientific Corporation, Natick, MA, USA). IVUS volumetric analysis of the target lesions was conducted by using a 20-mm segment at the lesion site for analysis.…”
Section: Intravascular Imaging and Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of this procedure and its reproducibility were previously described. 5 IUVS measurements were performed with a 2.6F, 40-MHz Atlantis Pro IVUS catheter (Boston Scientific Corporation, Natick, MA, USA). IVUS volumetric analysis of the target lesions was conducted by using a 20-mm segment at the lesion site for analysis.…”
Section: Intravascular Imaging and Evaluationmentioning
confidence: 99%
“…The details of IVUS volumetric analysis have been also described previously. 5 Data for plaques that underwent angioscopic color assessment and IVUS volumetric analysis at baseline, week 28, and week 80 were defined as "matched data". When multiple yellow plaques were included in a single 20-mm IVUS analysis segment, the mean color grade was used.…”
Section: Intravascular Imaging and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Statin treatment is known to reduce both plaque volume evaluated by IVUS and yellow color evaluated by angioscopy 20,21 . However, it has not been clarified which of plaque volume and plaque color is more directly associated with the risk of plaque disruption or the risk of ACS.…”
Section: Regression Of Vulnerable Plaques By Statin Treatmentmentioning
confidence: 99%
“…Subanalysis in our previous study (6) revealed that statin treatment was effective to reduce ACS events in the patients with multiple yellow plaques but not in the patients with fewer yellow plaques. Therefore, it is reasonable that statin treatment is more effective in CKD patients than in non-CKD patients (15) because it may reduce cardiac events by the regression and stabilization of vulnerable plaques (16).…”
Section: Ckd and The Risk Of Cardiovascular Eventsmentioning
confidence: 99%